Risk perception: how previous experiences influence the assessment of risk by immigrants in South Africa - Sibanda, Pearson (Graduate School of Business (GSB), 2019)
Opportunity recognition and evaluation, or indeed creation, have been identified as critical for new venture creation. Studies have shown that they are mediated by risk perception, with some scholars arguing that the difference between entrepreneurs and non-entrepreneurs lies in how they perceive risk. It has also been argued that immigrants are more entrepreneurial than the indigenous population, a finding confirmed by studies of entrepreneurial firms in Silicon Valley in the United States of America. It has been suggested that if all immigrants in the world lived in one country, it would be the sixth most populous in the world. This is what makes the study of immigrant entrepreneurs essential, with a view to finding out what drives risk perception amongst them. The central question that this study intended to answer was: “How do immigrants’ previous experiences in their countries of origin, as well as their experiences in transit to and on arrival in South Africa, influence their risk perception?” A qualitative study involving 36 immigrants drawn from the rest of Africa and the Indian subcontinent was undertaken in various cities throughout South Africa. The study used the Grounded Theory methodology, through which data collected from semi-structured interviews were processed. Using a constructivist epistemological stance the data were then interpreted, resulting in a model for risk perception that built on other well-known models. The study found that previous experiences, hardships, youth and individualism do influence risk perception both directly and indirectly. This is in addition to having limited choices, limited government support and a desire for independence, which were also found to influence risk perception. The study therefore contributes to theories on, and the understanding of, risk perception, and by extension new venture creation. However, no support was found for the often stated view that immigrants become entrepreneurs because they cannot access the job market. Although the study was conducted on immigrant entrepreneurs, the findings may well be applicable to any other group. This would need to be confirmed by further studies. In addition further studies would be needed to establish how this knowledge can be used in efforts to encourage entrepreneurship.